Answers

2015-03-13T18:22:04+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Now in triangles AXE and CXE,
XE is the median and divides the triangle int two triangles of equal area
Thus, ar(AXE) = ar(CXE)

Now in triangle ABC,
BE is the median thus ar(ABE) = ar(BCE)
= ar(ABX) + ar(AXE) = ar(BXC) + ar(CXE) {Sustituting ar(ABE)= ar(BCE)}
NOw as ar(AXE) = ar(CXE), they get cut. Thus we have:
ar(ABX) = ar(BXC) 
 
Hope that helps !!
3 5 3